Imaging modalities for biological and preclinical research. a compendium - Walter, Andreas; Mannheim, Julia; Caruana, Carmel J. (IOP (Series). Release 21., 2021)
The relentless pace of innovation in biomedical imaging has provided modern researchers with an unprecedented number of techniques and tools to choose from. While the development of new imaging techniques is vital for ongoing progress in the life sciences, it is challenging for researchers to keep pace. Imaging Modalities for Biological and Preclinical Research is designed to provide a comprehensive overview of currently available biological and preclinical imaging methods, including their benefits and limitations. Experts in the field guide the reader through both the physical principles and biomedical applications of each imaging modality, including description of typical setups and sample preparation. Volume 1 focuses on ex vivo imaging. It covers all available advanced and basic light and fluorescence microscopy modalities, X-ray, electron, atomic force and helium ion microscopy, dynamic techniques such as fluorescence recovery after photobleaching as well as spectroscopic techniques such as coherent Raman imaging or mass spectrometry imaging. Part of IPEM-IOP Series in Physics and Engineering in Medicine and Biology.